Analisis Tegangan Tarik Maksimum Wire Rope pada Hoist Crane Kapasitas 3 Ton - Andri, Rezky; Nurdin, Hendri (Lembaga Yasin AlSys, 2024)
Steel ropes are one of the most important parts of a lifting aircraft system. The strength of the steel rope varies, depending on the use and needs. A typical steel rope construction for elevators consists of 8 spins wrapped together, heading left or right with a core in the middle. Each steel rope spin consists of 19 wires which is 9.9.1, meaning 9 wires outside, 9 inside and 1 in the center. The cross-sectional area of steel rope (F152) based on the tensile stress for one steel rope (S) is 1.9 cm. The tensile stress that occurs on the steel rope is (S) = 1773 kg. While the permissible tensile stress is (Smax) = 2800 kg. The actual steel rope breaking strength (P) based on the safety factor with mechanism type and operating conditions (K) is (P) = 9753 kg. Steel rope used type: 8 x 19 = 152 + 1 Fiber Core with specifications: steel rope diameter (d) : 10 mm, rope weight (W) : 1.15 kg / m, steel rope breaking load (Pb) : 15,400 kg, rope breaking stress (σb) : 140-159 kg / mm². Because the tensile stress (S) = 1773 kg is smaller than the permissible tensile stress (Smax) = 2800 kg, it can be concluded that the steel rope is safe against the tensile load that occurs.